Evaluation of Season-Long Weed Management Programs in Red Beet. (December 2016) - Colquhoun, Jed B.; Heider, Daniel J.; Rittmeyer, Richard A.
Abstract : Red beet growers have expressed interest in adopting the microrate herbicide approach originally implemented in sugarbeet to achieve season-long weed management. Several red beet herbicides were first labeled for use in sugarbeet and lack substantial residual weed control. In response, red beet herbicide programs were evaluated that included a PRE application followed by up to three POST applications of various herbicide combinations. This research, however, indicated that herbicide programs that included PRE herbicides followed by as few as one or two POST applications that involve multiple active ingredients can provide season-long weed control. This observation was consistent across a broad spectrum of weeds, between two study locations that varied in soil type, and during two growing seasons. Herbicide programs that included only a PRE and six-leaf red beet growth stage application were successful at two locations in maintaining weed control and crop yield relative to hand-weeded red beet. Furthermore, these herbicide programs reduced the number of applications by 50% compared with the full programs, reducing crop injury risk and grower cost.